KAJIAN LITERATUR PENGEMBANGAN FLASHCARD DIGITAL MULTISENSORI DALAM PEMBELAJARAN MEMBACA PERMULAAN DI SEKOLAH DASAR - Yoshev Fauzha Beladona; Sri Sumartiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Early reading ability is a fundamental foundation for students’ academic success in primary education. However, studies indicate that early literacy skills among Indonesian students remain low, necessitating innovative learning approaches that integrate technology and multisensory methods. This study aims to examine the trends, effectiveness, and design of digital multisensory flashcards in improving early reading skills among lower-grade elementary students. The research employed a Systematic Literature Review (SLR) with a descriptive-analytical approach, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were collected from major academic databases such as Google Scholar, ERIC, DOAJ, and SINTA, encompassing 42 articles published between 2015 and 2025. The findings reveal that the use of digital multisensory flashcards effectively enhances letter recognition, phonemic awareness, and vocabulary acquisition through the integration of visual, auditory, and kinesthetic elements. Moreover, interactive digital media improves students’ motivation, memory retention, and learning focus. In conclusion, digital multisensory flashcards hold great potential for enhancing early literacy instruction, particularly when supported by teacher training and adequate digital infrastructure. Future research is recommended to explore adaptive learning technologies and local cultural contexts to ensure greater relevance and applicability in Indonesian primary education.